2022
DOI: 10.3390/pr10061207
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Characterization of a Functionalized Cotton Fabric with Nanocomposite Based on Silver Nanoparticles and Carboxymethyl Chitosan Using Green Chemistry

Abstract: Cotton is the most widely used natural fiber for textiles but its innate capacity to absorb moisture, retain oxygen, and high specific surface area make it more prone to microbial contamination, becoming an appropriate medium for the growth of bacteria and fungi. In recent years, the incorporation of silver nanoparticles in textile products has been widely used due to their broad-spectrum antibacterial activity and low toxicity towards mammalian cells. The aim of the current study is to synthesize and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…Our research group has previously synthesized and characterized functionalized cotton fabric with silver nanoparticles and carboxymethyl chitosan (AgNPs-CMC) [131,132]. The nanocomposite obtained from the complex [Ag (NH 3 ) 2 ] + was synthesized under similar conditions and verified the formation of silver nanoparticles [131]. Our results, as characterized by Dynamic Light Scattering (DLS) for AgNO 3 , revealed a monodisperse distribution of the nanocomposite with an average hydrodynamic size of 166.7 nm [131].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Our research group has previously synthesized and characterized functionalized cotton fabric with silver nanoparticles and carboxymethyl chitosan (AgNPs-CMC) [131,132]. The nanocomposite obtained from the complex [Ag (NH 3 ) 2 ] + was synthesized under similar conditions and verified the formation of silver nanoparticles [131]. Our results, as characterized by Dynamic Light Scattering (DLS) for AgNO 3 , revealed a monodisperse distribution of the nanocomposite with an average hydrodynamic size of 166.7 nm [131].…”
Section: Introductionmentioning
confidence: 62%
“…Our results, as characterized by Dynamic Light Scattering (DLS) for AgNO 3 , revealed a monodisperse distribution of the nanocomposite with an average hydrodynamic size of 166.7 nm [131]. Fourier Transformation Infrared spectroscopy (FT-IR) demonstrated the inhibition of spec-tral bands at 879 and 723 cm −1 indicating the presence of AgNPs in the nanocomposite [131]. Scanning electron microscopy (SEM) demonstrated that the silver nanoparticles were spherical in shape and between 5 and 20 nm [131].…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations